Kajian Sosiologi Sastra Dalam Naskah Drama Ambu Hawuk Karya AB Asmarandana dan Pemanfaatannya Untuk Bahan Ajar Jenjang SMP - Pani Aulia Rukmana; Fany Haifa Alia; Nandang Kurnia Sandi; Adita Widara Putra (Simpati, 2024)
This research aims to analyze and describe sociological studies in the drama script "Ambu Hawuk" by Ab Asmarandana. The method used in this research is a qualitative descriptive method. The data produced in qualitative methods is mostly in the form of words, not a series of numbers. The main data source that was directly collected by researchers was the drama script "Ambu Hawuk" by Ab Asmarandana. Data collection in this research used library, listening and note-taking techniques. The library technique is a technique used to obtain data from written sources, while the listening and note-taking technique shows that researchers carry out careful, directed and careful listening while collecting data by utilizing the analysis guidelines that have been formulated. The study used in this research uses sociological studies of literature. The results of this research show that the drama script "Ambu Hawuk" by Ab Asmarandana has a relationship with the study of literary sociology, namely it is based on works based on the author. This story is based on the Galungung Suakkerta area. Galunggung is a volcano located about 17 km from the center of Tasikmalaya City. Apart from that, there are several findings that reflect that this story is from the Sundanese tribe because the language used is Sundanese. This manuscript is a work drawn from the author from the local area and local cultural diversity. So if the drama script "Ambu Hawuk" by Ab Amarandana is used as teaching material for junior high school students, they will know and fully understand the meaning that the author wants to convey. So, an ecosystem for preserving and maintaining local cultural values will be built by the younger generation.